MOLECULAR MECHANISMS AND CLINICAL SIGNIFICANCE OF EPITHELIAL TISSUE CELLS ADAPTATION TO HYPOXIA - Khalilov Hikmatulla Dilshod oglu; Tilyabov Ikrom; Berdiev Otabek Vahob oglu (Western European Studies, 2025)
Epithelial tissue covers the internal and external surfaces of the body and performs important functions such as protection, secretion, absorption and signaling. This article deeply studies the mechanisms of adaptation of epithelial cells to various stress conditions (hypoxia, inflammation, mechanical deformation, chemical effects). Epithelial cell adaptation occurs at the molecular, genetic and cellular physiological levels and is carried out through pathways such as HIF-1α, NF-κB, EMT (epithelial-mesenchymal transition). Activation of the HIF-1α factor under hypoxia conditions changes the energy metabolism of cells and ensures their survival. Activation of the NF-κB pathway during inflammatory processes leads to the production of cytokines and chemokines, which in turn enhances the immune response. The EMT process plays an important role in the development of metastatic cancer, causing epithelial cells to acquire mesenchymal properties. Disruption of these adaptive mechanisms can lead to various pathologies (delayed wound healing, ulcers, cancer metastasis). Therefore, understanding the adaptive capacity of epithelial cells can be the basis for the development of new therapeutic methods
Keywords: Epithelial tissue; adaptation; intercellular signaling